New insights into viral threats in soybean (Glycine max) crops from Bangladesh, including a novel crinivirus - Khatun, Mst. Fatema; Kwak, Myeonghwan; Kwon, Minhyeok; Hossain, Md. Motaher; Kil, Eui-Joon (Frontiers in Microbiology, 2025)
Soybean (Glycine max) crops in Bangladesh face significant challenges due to viral diseases, exacerbated by the hot and humid conditions that favor virus and vector proliferation. The emergence of novel or resurgent viruses can jeopardize soybean production because of the difficulties in identifying and characterizing these pathogens. In addition, detecting and characterizing new plant viruses demands considerable resources and commitment. This study examines soybean plants, collected from research fields in Gazipur, Bangladesh, between February 2022 and January 2023, that exhibited green or yellow mosaic, leaf wrinkling, and mild yellowing symptoms. Utilizing high-throughput sequencing, we examined the virome in soybean leaves. Our findings revealed the presence of three RNA viruses—Potyvirus phaseovulgaris (bean common mosaic virus, BCMV), P. phaseoli (bean common mosaic necrosis virus, BCMNV), a novel crinivirus—and one DNA virus, Begomovirus vignaradiataindiaense (mungbean yellow mosaic India virus, MYMIV). This is the first identification of the novel crinivirus, soybean mild yellows Bangladesh virus (SMYBV), in soybean. We assembled four viral genome sequences for phylogenetic analysis. The novel crinivirus is closely related to the criniviruses CCYV, LCV, and PloACV. BCMV and BCMNV exhibited high sequence similarity with a Bangladeshi isolate in the common bean, which indicated the continued spread of BCMV and BCMNV present in Bangladesh. Mixed infections with MYMIV-SMYBV, MYMIV-BCMV-BCMNV, and MYMIV-BCMNV were detected in soybean samples through RT-PCR and PCR.